Territorial competitiveness in a globalised economy: Regional efficiency of the Mexican service sector - Alejandra Trejo (European Regional Science Association (ERSA), 2010)
It is argued that the competitive capacities from the regional and local point of view can be constructed, that in fact are tied to territorial policies and to the development of a territorial culture that integrates the local system of companies. Moreover a process of such nature can contribute to overcome the deterioration of backward territories. The construction of territorial competitiveness has to be one along the fundamental lines of action of sub-national governments. The existence of a solid service sector and some degree of specialisation in tertiary activities are among a number of territorial diversity of factors which need to be taken into account in relation to the creation of competitive capacities. In addition globalisation has presumably played a significant role in the productive restructuring of economies; within this the service sector has had over the years an increasing quantitative and qualitative importance in economic structures. This urges to evaluate the role of the third sector, in a context of economic globalisation, in the processes of constructing regional competitive capacities. This paper aims at providing a wide-ranging assessment of efficiency of the third sector at the regional level and its sources as well as an examination of the territorial structure of services and commerce in Mexico, specialisation patterns and productive structures. Our interest is to begin a line of study to analyse the efficiency of the Mexican tertiary sector by looking at the differences in regional performance and also the geographical determinants of these differentials. We will evaluate if there are clear patterns of concentration, specialisation and regional efficiency because of its impact on regional competitiveness. The regional efficiency of the service sector in Mexico in the period of NAFTA operation will be analysed. We employ state level data to examine technical efficiency's differentials across regions and their determinants. The methodology includes Data Envelopment Analysis to measure the efficiency of the third sector which is the dependent variable in a reduced form model that links regional performance with a number of proxies for various types of agglomeration economies such as specialisation, urbanisation and internal economies of scale.
Keywords: 330